Obligations of Notaries in Providing Free Legal Services to People Who Are Poor - Yustisianto, Dwi; Hafidz, Jawade (Sultan Agung Notary Law Review, 2023)
This research aims to analyze: 1) Notaries' obligations to provide free legal services to people who cannot afford it. 2)      Legal sanctions for notaries who refuse to provide free legal services to people who cannot afford it.The approach method used in this research is a qualitative approach. This type of research falls within the scope of sociological juridical research. The types and sources of data in this research are primary and secondary data obtained through interviews and literature study. The analysis in this research is descriptive qualitative. The results of the research concluded: 1) The obligation of a notary to provide free legal services to people who cannot afford it is contained in Article 37 paragraph (1) UUJN, that notaries are obliged to provide legal services in the field of notarial services free of charge to people who cannot afford it. This article shows that people who cannot afford it can be given free notary services. The obligation of notaries to provide free legal services to poor people in Article 37 paragraph (1) UUJN gives hope that poor people can still get services from notaries. However, this norm is vague and unclear, this is because there is no clear explanation of the meaning of this article, and there are no other regulations that explain this matter. Providing free legal services in the notarial field from the Notary is based on confidence because there is an assumption that initially arises based on the Notary's assessment regarding the appearance and legal services required by clients who come to him, so that from that assessment the Notary can make a decision to provide services free legal services. And the client's candor towards the Notary is due to the honesty conveyed by the client regarding his inability to pay the honorarium for the legal services he requires. 2) Legal sanctions for notaries who refuse to provide free legal services to people who cannot afford them include sanctions such as verbal warnings, written warnings, temporary suspension, respectful dismissal, dishonorable and respectful dismissal. Sanctions are a form of government action, so that Notaries carry out Article 37 (1) UUJN in accordance with applicable regulations.